A study of variations in the origin of obturator artery in the human cadavers and its clinical significance - Sanjeev Kumar; Smita Minz (Wolters Kluwer Medknow Publications, 2017)
Background and aims: Study of origin of obturator artery, its variable origin and course is significant as knowledge attained by such studies help surgeons to avoid injuries, hemorrhage during operative procedures. Present study is aimed at finding out the variable origin of obturator artery, clinical significance and to correlate its embryological basis. Materials and Methods: Present study was conducted on 60 formalin fixed hemi section of cadaveric pelvis, which were allotted to the under graduate students of Mandya Institute of Mcdical Sciences, Mandya. Observations obtained were compared with the studies of previous workers. Results: Normal pattern of origin, from the anterior division of internal iliac artery was seen in 40% (24 cadavers). In 60% of the cadavers variations were observed. The most common variant mode of origin was from inferior epigastric artery (18.3%). Next common was origin from superior gluteal artery and least common variant of origin was from inferior vesical artery. Conclusion: Variations observed in present study were at par with the variations observed by previous studies. Although anomalous origins of the obturator artery rarely produces clinical symptoms, their knowledge is necessary for operating surgeons to avoid injuries and is of academic interest.